2014
DOI: 10.1007/s00038-014-0594-2
|View full text |Cite
|
Sign up to set email alerts
|

Health system challenges for the management of cardiovascular disease and diabetes: an empirical qualitative study from Syria

Abstract: We conclude that lack of effective management of CVD and diabetes indicated weaknesses of the state and its retracting role in providing effective healthcare. Such weaknesses that existed before the crisis are now compounded by new challenges resulting from wide destruction of the health system due to the ongoing war. The rebuilding of post-conflict heath care system may benefit from insights into the structural problems of the pre-crisis system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…The study on CVD mortality forecast in 2015 has shown that the MENA region will not achieve the target of 25% reduction of CVD mortality by 2025 without achieving all major targets for risk factor reduction (i.e., reducing the prevalence of elevated systolic blood pressure by 25%, reducing the prevalence of smoking by 30%, halting the rise in elevated body mass index, and halting the rise in fasting plasma glucose). Moreover, reports of health system challenges in controlling and managing CVD in some of the EMR countries reemphasize the need for significant investment and improvement of access (Roth et al 2015a , b ; Romdhane et al 2015 ; Ahmad et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study on CVD mortality forecast in 2015 has shown that the MENA region will not achieve the target of 25% reduction of CVD mortality by 2025 without achieving all major targets for risk factor reduction (i.e., reducing the prevalence of elevated systolic blood pressure by 25%, reducing the prevalence of smoking by 30%, halting the rise in elevated body mass index, and halting the rise in fasting plasma glucose). Moreover, reports of health system challenges in controlling and managing CVD in some of the EMR countries reemphasize the need for significant investment and improvement of access (Roth et al 2015a , b ; Romdhane et al 2015 ; Ahmad et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have used models to categorise factors influencing policy creation, adoption and adaptation, including Walt and Gilson’s framework [ 34 36 ] or Kingdon’s agenda-setting streams [ 37 ]. The framework for this study (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The problem of lack of political and managerial stability is observed in the majority of developing countries. Examples include Syria and Tunisia [36,37]. Also, the effects of the political climate on health policies in Pakistan show that the rapid change of the governments affects the policies, causing the imperfect implementation of various policies [38].…”
Section: Discussionmentioning
confidence: 99%